1994
DOI: 10.3168/jds.s0022-0302(94)77311-2
|View full text |Cite
|
Sign up to set email alerts
|

Flows of Nitrogen and Amino Acids in Dairy Cows Fed Diets Containing Supplemental Feather Meal and Blood Meal

Abstract: Four Holstein cows, fitted with ruminal and duodenal cannulas, were used to determine the effects of supplemental feather meal and blood meal on ruminal fermentation and flows of N and AA to the duodenum. The basal diet contained (DM basis) 9.9% chopped alfalfa hay, 39.7% corn silage, 34.7% cracked corn, 8.2% corn starch, 2.1% vitamins and minerals, 4.4% casein, and 1% urea. A combination of feather meal and blood meal (3:1 on an N basis) was used to replace 0, 33, 67, and 100% of the casein and urea in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…In contrast to the linear decrease of the apparent total-tract digestion of N as supplemental feather meal plus blood meal was increased in dairy rations (Cunningham et al, 1994), no significant difference between diets was observed with regard to the apparent digestibility of N in the study reported here. Apparent N digestibility was 1 percentage unit lower in the control (0% UIP) diet when compared with the other three diets.…”
Section: Composition Of Diets Dietary Ingredient Quantitiescontrasting
confidence: 98%
“…In contrast to the linear decrease of the apparent total-tract digestion of N as supplemental feather meal plus blood meal was increased in dairy rations (Cunningham et al, 1994), no significant difference between diets was observed with regard to the apparent digestibility of N in the study reported here. Apparent N digestibility was 1 percentage unit lower in the control (0% UIP) diet when compared with the other three diets.…”
Section: Composition Of Diets Dietary Ingredient Quantitiescontrasting
confidence: 98%
“…13,26 FM could be a good source of escape protein, however, increasing¯ow of non-ammonia nitrogen to the small intestine and supplying sulphur amino acids among others. 11,27 Limited digestibility has also been indicated in FM with in vivo studies, 28 but FM PDA-treated at 50% moisture content (Fig 1) meets the requirement of supplying both a substantial and, at the same time, constant amount of ammonia in the rumen so that it does not become limiting and ®bre digestion is optimised. At 12 h of digestion, protein disappearances of FM treated at 1-50-75, 1-50-90 and 2-50-90 processing conditions were 311, 371 and 430 g kg À1 , respectively, and were much higher (p`0.05) than FM PDA-treated at 10% moisture and the control (equal to or lower than 236 g kg À1 ).…”
Section: Resultsmentioning
confidence: 97%
“…Subsequently, groups of comparisons were tested for homogeneity between and within groups. All data were taken or calculated from experiments reported in 57 independent studies (Kung et al, 1983;Stern et al, 1983;Prange et al, 1984;Robinson and Sniffen, 1984;Santos et al, 1984;Robinson et al, 1985;Rode et al, 1985;Stern et al, 1985;Armentano et al, 1986;Lu et al, 1988;Price et al, 1988;McCarthy et al, 1989;Waltz et al, 1989;Herrera-Saldana et al, 1990;King et al, 1990;Klusmeyer et al, 1990Klusmeyer et al, , 1991aCameron et al, 1991;Lynch et al, 1991;Ohajuruka et al, 1991;Stokes et al, 1991;Erasmus et al, 1992Erasmus et al, , 1994Aldrich et al, 1993;Christensen et al, 1993aChristensen et al, , 1996Cunningham et al, 1993Cunningham et al, , 1994Cunningham et al, , 1996Feng et al, 1993;Poore et al, 1993;Tice et al, 1993;Benchaar et al, 1994;Pantoja et al, 1994Pantoja et al, , 1995Calsamiglia et al, 1995;Oliveira et al, 1995;Overton et al, 1995;Yoon and Stern, 1996;Chan et al, 1997;…”
Section: Statistical Analysis Of Data From Literaturementioning
confidence: 99%